Applied photonics - Yeh, Chai (Academic Press, 1994)
Photonic circuitry is the first-choice technological advancement recognized by the telecommunications industry.Due to the speed, strength, and clarity of signal, photonic circuits are rapidly replacing electronic circuits in a range of applications.